2014
DOI: 10.3892/br.2014.266
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human sirtuin 6 gene promoter methylation during aging

Abstract: Aging is a natural process during which changes at the cellular level increase death risk by developing susceptibility to a variety of diseases. Sirtuins have been shown to regulate lifespan in various organisms by deacetylating a number of important transcription factors. Of the 7 identified mammalian sirtuins (SIRT1-7), SIRT6 depletion is associated with severe symptoms of premature aging. In this study, we investigated the association between human longevity and promoter methylation. Genomic DNA from blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…CpG sites can regulate the effect of transcription via changing methylation states[3133]. In the current study, analyses of CGI sites demonstrated that the gene regions whose methylation level changed from prepuberty to puberty were gene bodies, intergenic regions, introns and exons, rather than promoter regions, which is not consistent with previous reports[34]. These CGI sites that were not located in the promoter may exert an important effect on regulating gene expression[35].…”
Section: Discussioncontrasting
confidence: 95%
“…CpG sites can regulate the effect of transcription via changing methylation states[3133]. In the current study, analyses of CGI sites demonstrated that the gene regions whose methylation level changed from prepuberty to puberty were gene bodies, intergenic regions, introns and exons, rather than promoter regions, which is not consistent with previous reports[34]. These CGI sites that were not located in the promoter may exert an important effect on regulating gene expression[35].…”
Section: Discussioncontrasting
confidence: 95%
“…This notion fits well with the early appearance of CGIs during vertebrate evolution and is associated with an increased concentration of CGIs close to TSSs from cold-blooded vertebrates to warm-blooded vertebrates [53]. To the best of our knowledge, this general trend has not been assessed in SIRT genes, but interestingly, the occurrence of CGIs has been reported in SIRT promoters of humans [54][55][56][57][58], mice [59] and ruminants [60][61][62]. In contrast, in GSB, the occurrence of CGIs was only found in sirt1 and sirt3.…”
Section: Cgis In Sirt Promoters Appeared Early During Vertebrate Evolsupporting
confidence: 77%
“…Age-dependent downregulation of SIRT1 favours acetylation of nuclear factor (NF)-kB p65, leading to its nuclear translocation and transcription of inflammatory genes (Yeung et al 2004). Recent work has shown that sirtuin expression can be modulated by epigenetic changes, namely increased DNA methylation and non-coding RNAs such as miR-200a and miR-34a (Eades et al 2011;Sahin et al 2014;Yu et al 2015). The maintenance of SIRT1 homeostasis is fundamental to repression of detrimental pathways of arterial ageing such as the Forkhead transcription factor (FOXO) pathway (Brunet et al 2004).…”
Section: Sirt1mentioning
confidence: 99%